IS LAPAROSCOPIC REOPERATION FEASIBLE TO TREAT EARLY COMPLICATIONS AFTER LAPAROSCOPIC COLORECTAL RESECTIONS? - PINTO,Rodrigo Ambar (2020)
ABSTRACT Background: Recently, with the performance of minimally invasive procedures for the management of colorectal disorders, it was allowed to extend the indication of laparoscopy in handling various early and late postoperative complications. Aim: To present the experience with laparoscopic reoperations for early complications after laparoscopic colorectal resections. Methods: Patients undergoing laparoscopic colorectal resections with postoperative surgical complications were included and re-treated laparoscopically. Selection for laparoscopic approach were those cases with early diagnosis of complications, hemodynamic stability without significant abdominal distention and without clinical comorbidities that would preclude the procedure. Results: In four years, nine of 290 (3.1%) patients who underwent laparoscopic colorectal resections were re-approached laparoscopically. There were five men. The mean age was 40.67 years. Diagnoses of primary disease included adenocarcinoma (n=3), familial adenomatous polyposis (n=3), ulcerative colitis (n=1), colonic inertia (n=1) and chagasic megacolon (n=1). Initial procedures included four total proctocolectomy with ileal pouch anal anastomosis; three anterior resections; one completion of total colectomy; and one right hemicolectomy. Anastomotic dehiscence was the most common complication that resulted in reoperations (n=6). There was only one case of an unfavorable outcome, with death on the 40th day of the first approach, after consecutive complications. The remaining cases had favorable outcome. Conclusion: In selected cases, laparoscopic access may be a safe and minimally invasive approach for complications of colorectal resection. However, laparoscopic reoperation must be cautiously selected, considering the type of complication, patient’s clinical condition and experience of the surgical team.